Domestic bioethanol-fireplaces-a new source of severe burn accidents - Neubrech, Florian G.; Kiefer, Jurij; Schmidt, Volker-Jürgen; Bigdeli, Amir Khosrow; Hernekamp, Jochen-Frederick; Kremer, Thomas; Kneser, Ulrich; Radu, Christian Andreas (Burns, 2016)
Background - Bioethanol-fueled fireplaces are popular interior home decoration accessories. Although their safety is promoted frequently, actual presentations of severe burn injuries in our burn intensive care unit (ICU) have focused the authors on safety problems with these devices. In this article we want to explore the mechanisms for these accidents and state our experiences with this increasingly relevant risk for severe burn injuries. - Materials and Methods - The computerized medical records of all burn intensive care patients in our burn unit between 2000 and 2014 were studied. Since 2010, 12 patients with bioethanol associated burn injuries were identified. Their data was compared to the values of all patients, except the ones injured by bioethanol fireplaces that presented themselves to our burn ICU between the years 2010 and 2014. - Results - At time of admission the bioethanol patients had a mean ABSI-score of 4.8 (+/− 2.2 standard deviation (SD)). A mean of 17 percent (+/− 9.1 SD) body surface area was burned. Involvement of face and hands was very common. An operative treatment was needed in 8 cases. A median of 20 days of hospitalization (range 3-121) and a median of 4.5 days on the ICU (range 1-64) were necessary. No patient died. In most cases the injuries happened while refilling or while starting the fire, even though safety instructions were followed. In the control group, consisting of 748 patients, the mean ABSI-score was 5.6 (+/− 2.7 SD). A mean of 16.5 percent (+/- 10.1 SD) body surface area was burned. Treatment required a median of 3 days on the burn ICU (range 1-120). Regarding these parameters, the burden of disease was comparable in both groups. - Conclusion - Bioethanol-fueled fireplaces for interior home decoration are a potential source for severe burn accidents even by intended use.
Published 2015
Gesehen am 26.01.2021